Climate Anomalies and International Migration: A Disaggregated Analysis for West Africa - Arndt Reichert; Fernanda Martinez Flores; Sveta Milusheva (ZBW - Leibniz Information Centre for Economics, 2021)
West Africa is vulnerable to negative impacts of climate change and a potential channel of adjustment is migration. Using novel geo-referenced and high-frequency data, we investigate the extent to which soil moisture anomalies have an impact on international migration within the region and directed to Europe. Our findings show that drier soil conditions decrease rather than increase the probability to migrate. A standard deviation decrease in soil moisture leads to a 2 percentage points drop in the probability to migrate, which is equivalent to a decrease of about 25% in the number of migrants. This effect is concentrated during the crop-growing season, suggesting that the decrease in migration is mainly driven by financial constraints. The effect is only seen for areas that are in the middle of the income distribution, with no impact on the poorest or richest areas of a country.
Keywords: F22; O13; O15; Q54; 330; West Africa; climate change; migration; agriculture